EVALUATION OF PUBLIC SERVICE PERFORMANCE AND PUBLIC SATISFACTION AT THE NATIONAL LAND AGENCY SURABAYA - Budi Priyambodo; Ika Devy Pramudiana; Widyawati Widyawati; Damayanti Sri Lestari (DIA: Jurnal Administrasi Publik, 2026)
This study aims to evaluate public service performance and community satisfaction at the National Land Agency (BPN) Surabaya, using the theoretical framework proposed by Dwiyanto in his book Reformasi Administrasi Publik (Public Administration Reform). Five key performance indicators—productivity, service quality, responsiveness, responsibility, and accountability—are used as the basis for analyzing the extent to which BPN Surabaya meets the needs and expectations of the community. This qualitative study employs data collection methods such as in-depth interviews, community satisfaction surveys, and document analysis. The findings indicate that productivity at BPN Surabaya needs improvement, as data from 2023 shows that 26.6% of land certification applications experienced delays beyond the targeted completion time. In terms of service quality, 72% of the respondents felt that the waiting room facilities were inadequate, significantly hindering user comfort. Responsiveness also requires attention, with 68% of the respondents reporting slow or inaccurate responses to inquiries or complaints. Regarding responsibility, 62% of the respondents stated that information related to procedures and requirements was unclear, highlighting the need for better internal supervision. Furthermore, accountability also needs enhancement, with only 60% of the respondents believing that information about costs and procedures was transparent, and 55% indicating that the complaint mechanisms were ineffective.